Hemolytic disease of newborn following anti-C and anti-S alloimmunization: A case report with review of literature - Shrutiprajna Kar; Monalisa Pradhan; Tapas Som; Pankaj Kumar Mohanty (Wolters Kluwer Medknow Publications, 2023)
Background: Non-Rhesus D antigen non-ABO, minor blood group alloimmunization in pregnant women is being increasingly recognized as a significant contributor to the development of the hemolytic disease of the fetus and newborn (HDFN). We report severe HDFN in a neonate born to an Rh-positive mother with sickle cell disease, following anti-C and anti-S alloimmunization. Clinical Description: A male baby born to a repeatedly transfused mother with sickle cell disease developed severe jaundice at 22 h of life. The baby was found to have severe anemia and indirect hyperbilirubinemia, but no encephalopathy, hepatosplenomegaly, or features of sepsis. Management and Outcome: His blood group was O positive and the direct Coombs test was 4+. Minor blood group typing showed the presence of anti-C and anti-S antibodies. The baby improved after receiving a double-volume exchange transfusion with matched blood and phototherapy. Conclusion: Severe hemolytic disease of the newborn (HDN) may be caused by minor blood group alloimmunization, especially seen in mothers with a history of multiple transfusions. Antenatal screening for alloimmunization in high-risk mothers can ensure timely diagnosis and treatment of HDN and prevent the harmful effects of neonatal hyperbilirubinemia.